Establishing a GIS-SMCDA Model of Sustainable Eco-Tourism Development in Pahang, Malaysia - Azizan, Marzuki; Syed Milad, Bagheri Ghadikolaei; Azizul, Ahmad; Tarmiji, Masron; Mohd Fadzil, Mohd Akhir (International Union of Geological Sciences, 2023)
In this study on dynamic, complex, and spatial decision making situations, the geographic information system (GIS) based spatial multi-criteria decision analysis (SMCDA) is used as a tool for sustainable environmental planning and ecotourism spot study. GIS is used to identify and study the morphological zones of coastal resorts and ecotourism sustainability in Sungai Karang sub-district in Kuantan, Pahang. To evaluate the geographic information of the state, the development of geodatabase and spatial modeling were used as one of the most appropriate GIS-SMCDA models to create new dimensions for understanding the current situation in the identification of ecotourism-sensitive areas (ESA). The results in the final ESA map show that the size of the zones for the built-up area: 4,500.25 ha, agricultural area: 3,635.87 ha, coastline: 2,109.67 ha, road: 3,518.72 ha, and water bodies: 8,899.37 ha. The study suggests that the GIS-SMCDA model can be a quite effective method for dealing with different parameters of site attractiveness for ecotourism sustainability. The results show that the area of a suitable site for ecotourism in Sungai Karang Sub-district is 248.87 ha, compared to an unsuitable site of 29,104.44 ha. This shows that a minimum area can be selected for the construction of an ecotourism center in this area.